A Prospective Phase II Study of Simultaneous Modulated Accelerated Radiotherapy Concurrently With CDDP/S1 for Esophageal Squamous Cell Carcinoma in the Elderly - Guo, SuPing; Liu, FangJie; Liu, Hui; Wu, YingJia; Zhang, XuHui; Ye, WenFeng; Luo, GuangYu; Li, QiWen; Chen, NaiBin; Hu, Nan; Wang, Bin; Zhang, Jun; et al. (Frontiers in Oncology, 2021)
Background: To explore the efficacy and toxicity of simultaneous integrated boost intensity-modulated radiation therapy (SMART) concurrently with CDDP/S1 in elderly patients with esophageal squamous cell carcinoma (ESCC). Methods: This single-arm, phase II study enrolled pathologically confirmed, stage II–IVa ESCC of 70–80 years old and Eastern Cooperative Oncology Group performance status (ECOG PS) 0–2. Patients received SMART (64Gy in 30 fractions) with concurrent CDDP (day 1 of each week) and S1 (days 1–14, 22–35). The primary endpoint was objective response rate (ORR). The secondary endpoints included progression-free survival (PFS), overall survival (OS) and toxicities. Results: Thirty-seven eligible patients were analyzed with median follow-up of 25.7 months for all and 46.1 months for survivors. The ORR was 86.5%. Patients with baseline weight loss <5% (p=0.050) and nutritional risk index (NRI) ≥105.2 (p=0.023) had better tumor response. Median PFS was 13.8 months with 2-year PFS of 37.5%. Median OS was 27.7 months with 2-year OS of 57.5%. OS was significantly associated with ECOG PS (p=0.005), stage (p=0.014), gross tumor volume (p=0.004), baseline NRI (p=0.036), baseline CRP level (p=0.003) and tumor response (p=0.000). CRP level (p=0.016) and tumor response (p=0.021) were independently prognostic of OS. ≥grade 3 anemia, leukopenia and thrombocytopenia occurred in 2.7%, 24.3% and 13.5% of patients; ≥grade 3 esophagitis and pneumonitis occurred in 18.9% and 2.7% of patient, respectively. Conclusion: SMART concurrently with S-1/CDDP yielded satisfactory response rate, survival outcome and tolerable treatment-related toxicities in elderly patients with ESCC. Baseline nutritional and inflammation status help to predict treatment outcome.